A Computational Analysis of the Soret and Dufour Effects on a Rotating Hybrid Nanofluid - Prathiba, Alfunsa; Lakshmi, Venkata A.; Ramesh, V. (Communications in Mathematics and Applications, 2023)
This paper shows the impact of the Dufour and Soret numbers on a hybrid nanofluid (HNF) in a boundary layer area across a spinning sheet. The collection of flow governing (PDEs) partial differential equations was turned into a system of (ODEs) ordinary differential equations, which are then solved utilising BVP4C code in MATLAB. The impact of the flow governing parameters on the flow properties were analysed and presented graphically. The Soret factor influences the thermal efficiency at the surface, while the Dufour effect reduces the mass transfer at the surface.